1997
DOI: 10.1093/molehr/3.12.1087
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of intracellular calcium in the mouse egg injected with a spermatozoon

Abstract: Oscillatory rises in intracellular Ca2+ concentration ([Ca2+]i) are the pivotal signal in the fertilization of mammalian eggs. The spatiotemporal dynamics of [Ca2+]i rises in mouse eggs subjected to intracytoplasmic sperm injection (ICSI) were analysed by Ca2+ imaging and compared with those subjected to in-vitro fertilization (IVF). The first Ca2+ transient occurred 15-30 min after ICSI in most eggs, and was followed by Ca2+ oscillations which lasted for at least 6 h at intervals of approximately 10 min. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 30 publications
1
70
0
1
Order By: Relevance
“…2) show that an increased extent of polyspermy can be associated with this delay. An optimal, sperm-induced pathway of Ca 2C signaling may be important, as it is known that spatial and temporal characteristics of Ca 2C transients differ between eggs activated by IVF and eggs activated by parthenogenetic stimuli and also eggs fertilized by intracytoplasmic sperm injection (Nakano et al 1997, Sato et al 1999, Deguchi et al 2000. ICSI is pertinent here as it too, like parthenogenesis, has been reported to be unable to induce establishment of the membrane block (Maleszewski et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…2) show that an increased extent of polyspermy can be associated with this delay. An optimal, sperm-induced pathway of Ca 2C signaling may be important, as it is known that spatial and temporal characteristics of Ca 2C transients differ between eggs activated by IVF and eggs activated by parthenogenetic stimuli and also eggs fertilized by intracytoplasmic sperm injection (Nakano et al 1997, Sato et al 1999, Deguchi et al 2000. ICSI is pertinent here as it too, like parthenogenesis, has been reported to be unable to induce establishment of the membrane block (Maleszewski et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown that application of synthetic peptides containing RGD or KTC amino acid sequences, which are recognized by integrins, elicits [Ca 2+ ] i increases in Xenopus (Iwao and Fujimura, 1996;Shilling et al, 1997Shilling et al, , 1998 and bovine eggs (Campbell et al, 2000), neither egg surface receptors nor sperm ligands capable of mediating [Ca 2+ ] i responses have yet been identified. In addition, normal fertilization, as judged by the presence of [Ca 2+ ] i oscillations and development to term, can be achieved by direct injection of a sperm into the ooplasm (intracytoplasmic sperm injection; ICSI) (Kimura and Yanagimachi, 1995;Nakano et al, 1997;Kurokawa and Fissore, 2003), which bypasses the interaction of gamete membranes. Due to these shortcomings, the "fusion" hypothesis, a third hypothesis, was conceived, in which a soluble substance from the fertilizing sperm, called sperm factor (SF), is delivered into the ooplasm and triggers [Ca 2+ ] i oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…This is increasingly used as a method for overcoming male factor infertility associated with in vitro fertilization (IVF). Not only does ICSI lead to egg activation, but in human, mouse, pig and horse eggs it has been shown to trigger a fertilization-like series of Ca 2þ oscillations (Tesarik & Sousa 1994, Nakano et al 1997. These data, therefore, offer another line of support for the hypothesis that the sperm activates eggs by introducing a factor after fusion.…”
Section: Sperm Factors and Calcium Releasementioning
confidence: 74%